CAP-reform and the provision of non-commodity outputs in Brandenburg - Kathrin Happe; Martin Damgaard; Amanda Osuch; Claudia Sattler; Peter Zander; Sandra Uthes; Johannes Schuler; Annette Piorr (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2006)
This paper presents an attempt to model the response of selected farms to decoupled direct payments and the associated impact on the provision of a defined set of non-commodity outputs (NCO's) using a combined modelling approach consisting of the AgriPoliS and MODAM models. AgriPoliS focuses on the socio-economic dimension of multifunctionality at the individual farm and regional levels and explicitly models heterogeneous farms (in size, location and efficiency) within a competitive and dynamic environment. The linear-programming model MODAM allows a detailed representation of production processes and their impact on the environmental dimension of multifunctionality at the farm level. We simulate the impact of a uniform area payment and a fully decoupled single farm payment. Our case study region is the district Ostprignitz-Ruppin in Brandenburg. Results show that the decoupling schemes create a trade-off between the NCO's and that adjustment reactions differ between farms depending on their legal form, size, and production.
Keywords: 330; EU-Agrarpolitik; Agrarreform; Wirkungsanalyse; Agrarsubvention; Landwirtschaftliche Betriebsform; Agrarproduktion; Agrarboden; Simulation; Brandenburg; Agentenbasierte Modellierung